Effects of oyster mushroom (Pleurotus ostreatus) and nettle (Urtica dioica) methanolic extracts on immune responses and resistance to Aeromonas hydrophila in rainbow trout (Oncorhynchus mykiss) - Bilen, Soner; Ünal, Sabri; Güvensoy, Hatice (Elsevier BV, 2016)
Abstract In this study, immunostimulant effects of the methanolic extracts of oyster mushroom (Pleurotus ostreatus) and nettle (Urtica dioica), and disease resistance against Aeromonas hydrophila in rainbow trout (Oncorhynchus mykiss) were investigated. Three different concentrations of extracts [0 (Control), 0.1 and 0.5 g kg− 1 of feed] were individually mixed with the basal diet and fed to rainbow trout (10.28 ± 0.1 g) for a 30-day period. After 30 days feeding trial, rainbow trout was challenged with bacterial pathogen, A. hydrophila. Results showed that final fish weight and specific growth rate were higher in all treated groups compared to control group (P   0.05). Both in oyster mushroom and nettle extract administered groups, feed conversion ratio was lower than in control and the lowest level was in 0.1 g kg− 1 oyster mushroom group. All measured immune parameters were affected by the dietary intake of oyster mushroom and nettle extract (P  Myeloperoxidase activity was elevated in treated groups compared to control with the highest levels in nettle group. Moreover, rainbow trout treated with 0.1 and 0.5 kg− 1 nettle extract when challenged with A. hydrophila had the highest survival rate. No differences in survival were exhibited between control and oyster mushroom group. These results indicated an immunostimulatory and antimicrobial effects of oyster mushroom and nettle extracts in rainbow trout. However, cost-effectiveness of nettle places its better acceptance and application as an immunostimulant for rainbow trout. Statement of relevance This study was related with non-specific immune system of fish and effects of different medicinal plant or mushroom on it. The main aim was to investigate and find new and cost-effective immunostimulant for fish, especially for rainbow trout. It was also aimed to find a disease blocker for rainbow trout especially against A. hydrophila.
Keywords: 6. Clean water; 3. Good health